2019
DOI: 10.21865/ridep52.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Papel da Inteligência Emocional, Felicidade e Flow no Desempenho Académico e Bem-Estar Subjetivo em Contexto Universitário

Abstract: ResumoNo quadro da psicologia positiva, pretende-se explorar a relação entre Inteligência Emocional, Felicidade e Flow, e o desempenho académico e bem-estar subjetivo de estudantes universitários. A amostra inclui 215 participantes, com idades entre 18 e 58 anos (M=22.3; DP=4.91), maioritariamente de Ciências Sociais (55.9%), de diferentes cursos (1.º ao 6.º ano), e do género feminino (81,9%), sendo 18,1% trabalhadoresestudantes. Os instrumentos incluíram escalas de autorrelato (TEIQue, OHI, DFS-2 e JAWS), ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
2
10
0
9
Order By: Relevance
“…Trait EI was positively related to happiness and life satisfaction, confirming its criterion validity. These findings are in line with trait emotional intelligence theory (e.g., Petrides, 2001Petrides, , 2010Petrides et al, 2016) as well as with multiple previous studies from different contexts and cultures (e.g., Freudenthaler, Neubauer, Gabler, Scherl, & Rindermann, 2008 in Germany;Moutinho, Monteiro, Costa, & Faria, 2019 in Portugal; Stamatopoulou et al, 2016 in Greece;and Ye, Yeung, Liu, & Rochelle, 2019 in Hong Kong).…”
Section: Correlations and Hierarchical Regressionssupporting
confidence: 91%
“…Trait EI was positively related to happiness and life satisfaction, confirming its criterion validity. These findings are in line with trait emotional intelligence theory (e.g., Petrides, 2001Petrides, , 2010Petrides et al, 2016) as well as with multiple previous studies from different contexts and cultures (e.g., Freudenthaler, Neubauer, Gabler, Scherl, & Rindermann, 2008 in Germany;Moutinho, Monteiro, Costa, & Faria, 2019 in Portugal; Stamatopoulou et al, 2016 in Greece;and Ye, Yeung, Liu, & Rochelle, 2019 in Hong Kong).…”
Section: Correlations and Hierarchical Regressionssupporting
confidence: 91%
“…These skills can be acquired, learned and applied in the daily lives of young people, whether in the school context or in other contexts equally enriching in experiences and opportunities for the development of personal and interpersonal skills (Coelho and Sousa, 2018;Zelyurt and İnce, 2018). Authors such as Moutinho et al (2019) emphasize that these skills can be acquired with the support of the main agents involved in the educational environment such as families or the school. In other scientific studies, it is indicated that inclusive educational contexts originate that students develop higher academic performance (Diaz-Garolera et al, 2022), better relationships (Palardy, 2019), constructive conflict resolution (Hakvoort et al, 2022), cope with social problems more effectively and engage in inappropriate behaviors less frequently (Brossard Børhaug and Weyringer, 2019).…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…Entre os fundamentais fatores específicos ao curso de Engenharia que colaboram para o estresse nos estudantes estão a dificuldade em conciliar vida social e acadêmica, elevada carga horária, grande volume de matérias, competitividade entre estudantes, privação de sono, medo de adquirir doenças e cometer erros em seus estudos e trabalhos em campo, insegurança em relação ao mercado de trabalho e cobranças da sociedade e da instituição de ensino. Essas exigências têm efeitos negativos no bem-estar psicológico dos estudantes, podendo gerar, em especial, depressão e ansiedade (Ferreira, 2016;Moutinho, Monteiro, Costa, & Faria, 2020).…”
Section: Dificuldades Encontradas No Curso De Engenhariaunclassified